Genetic characterization and utilization of multiple Aegilops tauschii derived pest resistance genes in wheat - Hall, Marla Dale (Kansas State University, 2006)
Aegilops tauschii, the D-genome donor of modern wheat, has served as an important source of genetic variation in wheat breeding. The objective of this research was to characterize and utilize multiple Ae. tauschii-derived pest resistance genes contained in the germplasm KS96WGRC40. Two Ae. tauschii-derived genes, H23 and Cmc4, provide resistance to the Hessian fly (HF) and wheat curl mite (WCM), respectively. A linkage analysis of a testcross population estimated 32.67% recombination between H23 and Cmc4 on chromosome 6DS in wheat indicating that the two genes are not tightly linked as previous mapping reports show. Haplotype data of recombinant lines and physical mapping of linked microsatellite markers located Cmc4 distal to H23. Haplotype data indicated that both KS89WGRC04 and KS96WGRC40 have the distal portion of 6DS derived from Ae. tauschii. Microsatellite primer pairs BARC183 and GDM036 were more useful than the previously published linked markers in identifying lines carrying Cmc4 and H23, respectively. Through phenotypic selection and advancement within the testcross population, three TC1F2:4 lines were identified as homozygous resistant for H23 and Cmc4 and have the complete terminal segment of 6DS from Ae. tauschii. Two lines are more desirable than the original germplasm releases and can serve as a source of resistance to both HF and WCM in an elite background. A linkage analysis of a segregating recombinant inbred line population identified an Ae. tauschii-derived gene of major effect conferring resistance to Septoria leaf blotch (STB) and another Ae. tauschii-derived gene of major effect conferring resistance to soil-borne wheat mosaic virus (SBWMV) in the germplasm KS96WGRC40. The STB resistance gene in KS96WGRC40 is located in the distal 40% of the short arm of chromosome 7D flanked by microsatellite markers Xgwm044 and Xbarc126. Two previously reported STB genes, Stb4 and Stb5, have been mapped to 7DS in the same region as the STB resistance gene in KS96WGRC40. The uniqueness of the STB resistance genes on 7DS is questionable. The SBWMV resistance gene in KS96WGRC40 is located on chromosome 5DL linked to microsatellite marker Xcfd010. The SBWMV resistance gene within KS96WGRC40 was derived from TA2397 via KS95WGRC33.
Keywords: wheat genetics; pest resistance genes; Aegilops tauschii; molecular mapping; Hessian fly; wheat curl mite; Septoria tritici; soil-borne wheat mosaic virus; Agriculture, Agronomy (0285); Biology, Genetics (0369)